Об универсальных чертах сочинения - Левицкий, Юрий Анатольевич (Baltistica, 1989)
ON THE UNIVERSAL CHARACTER OF COORDINATIONThe two syntactic connections – coordination and subordination – differ not only in their form, but also in their meaning. Their meanings can be regarded from at least three aspects: logical, cognitive and communicative.Thus coordination and subordination are firstly correlated with the division of concepts and the definition of concepts, correspondingly. This difference is true for both word combinations and composite sentences. Secondly, the reversible coordination is correlated with the process of comparison, the irreversible coordination with the process of observation, and the subordination with the process of making conclusions. Thirdly, the two kinds of composite sentences can be presented as the result of monologization of two different kinds of dialogues.
Keywords: –